Analysis of time series an introduction - Chatfield Chris (Boca Raton Chapman & Hall, 2004)
It covers topics, including ARIMA probability models, forecasting methods, spectral analysis, linear systems, state-space models, and the Kalman filter. It also addresses nonlinear, multivariate, and long-memory models. This edition adds a section on han
Keywords: Time-series analysis